Formulation and Evaluation of Peel-Off Gel Mask and Face Mist from Noni Fruit Extract (Morinda citrifolia Linn.) Sub-Material Utilization of Cosmetic Plant-Based Biodiversity - Azizah , Nurul (JURNAL BIOEDUKATIKA, 2023)
Noni plants (Morinda citrifolia L.) can be found in the territory of Indonesia. The utilization of noni plants is not widely known by the Indonesian people. This plant has active compounds in the form of vitamin C, vitamin E, flavonoids, saponins, steroids, and alkaloids. The purpose of this study was to formulate and evaluate the preparation of peel-off gel mask and face mist produced. The diverse local potential of Indonesian plants needs to be integrated as a learning resource into the biology learning process. The goal is for students to realize the potential of their respective regions. Local potential can be explored through various biology teaching materials, one of which is teaching materials on the utilization of biodiversity. This type of research is experimental research. This study was conducted with the aim of making and evaluating a product, namely the preparation of peel-off gel mask and face mist from noni fruit extract. This research was conducted at the Biology Laboratory of Ali Maksum Krapyak High School, Yogyakarta and at Ahmad Dahlan University Pharmacy LAMDA (Analysis Laboratory). Noni fruit samples were taken from the Sleman area, Yogyakarta. The stages of this research were formulating noni fruit extract, preparation and physical evaluation of various organoleptic tests, pH tests, dry time tests, and spreadability and stickiness tests. The organoleptic test observation results of the peel-off gel mask are clear yellowish white, typical noni odor with jasmine perfume essence, thick and homogeneous shape. The pH value is 6. The dry time test is 20 minutes. The spreadability test is 5-7 cm and the stickiness test is 08.56 seconds. Organoleptical observation of face mist is clear white, typical odor of noni with essence jasmine, liquid form. The pH value is 5.5. The conclusion from these results is that the manufacture and evaluation of peel-off gel mask preparations and face mist from noni fruit extract (Morinda citrifolia Linn.) is safe to use and can be used as a learning resource for cosmetic plant-based biodiversity utilization sub-materials.